STRATEGI GURU KELAS DALAM MENGEMBANGKAN MINAT DAN BAKAT PESERTA DIDIK DI SDN RAHAYU - Hanifah Aulia Balqis; Patra Aghtiar Rakhman; Siti Rokmanah (STKIP Subang, 2023)
The development of students' interests and talents needs to be developed from an early age. Teachers as facilitators and motivators must be able to develop the potential interests and talents of their students. The purpose of this study was to find out how the teacher's strategy, especially the class teacher or homeroom teacher in developing the interests and talents of their students. By using a qualitative descriptive method with a case study approach, in which this research focuses more on the results of collecting data from sources, namely grade 4 teachers at SDN Rahayu and describing how the objective conditions regarding class teacher strategies in developing the interests and talents of students at SDN Rahayu. The results of this study indicate that the teacher's strategy in developing students' motivational interests and talents is appropriate, namely: 1) Approaching students, 2) Providing facilities and motivating them to take part in competitions, 3) Providing understanding by not forcing their will, and 4) Utilizing extracurricular activities at school.